Wine Production from Banana (Musa sapientum) Using Yeast (Saccharomyces cerevisiae) Isolated from Grape (Vitis vinifera). - Constance Chinyere Ezemba (International Journal of Applied Biology, 2022)
This research was carried out to produce wine from banana (Musa sapientum) using yeast (Saccharomyces cerevisiae) isolated from grape (Vitis vinifera). The fermentation of the banana wine lasted for 21days. During fermentation, liquor of the fermenting “must” were removed every 48hours from the fermentor for analysis of pH, titratable acidity, specific gravity and reducing sugar using standard procedures.. The results from the experiment showed that Specific gravity of the wine was observed to reduce drastically as the fermentation progresses. The pH of the Banana wine during fermentation increased from 4.16- 4.22 while the titrable acidity of the Banana wine produced increased from 1.05-1.77. The alcohol content of the wine increased from 0.0 to 9%. The higher the fermentation temperature, the faster the conversion of sugars into alcohol and carbon dioxide by the yeast. The flavor and taste was appreciable. This study showed that acceptable wine can be produced from banana with the yeast Saccharomyces cerevisiae isolated from grape.